Modelling of sustainable systems - Křupka Jiří; Mandys, Jan; Svobodová, Jana; Augustinová, Marie (Univerzita Pardubice, 2011)
This paper focuses on the issue of utilization of system approach in sustainability systems modelling. Into systems that deal with sustainability are included systems that research into regional quality of life. The proposed quality of life models work with real data for regions and districts in the Czech Republic. The models use decision trees and factor analysis methods.
Keywords: sustainability; system approach; quality of life; modelling; decision tree; multidimensional statistics methods